2020
DOI: 10.1002/pits.22432
|View full text |Cite
|
Sign up to set email alerts
|

Do students notice stress in teachers? Associations between classroom teacher burnout and students' perceptions of teacher social–emotional competence

Abstract: The goal of the present study was to investigate the link between elementary school teacher burnout and students' perceptions of teacher social-emotional competence (SEC). A total of 676 Grades 4-7 students in 35 classrooms rated their classroom teachers' SEC. In addition, teachers self-reported their current level of experienced burnout at work (i.e., depersonalization and emotional exhaustion). Multilevel analyses revealed significant classroom-level variability (i.e., 34%) in student-ratings of teacher SEC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 60 publications
(83 reference statements)
2
23
0
6
Order By: Relevance
“…Our results showed that negative affect has an important impact on teachers' health, by restraining the benefits of EI on burnout symptoms. These findings provide additional evidence that increasing emotional abilities are directly linked with lower levels of work-related stress (Extremera et al, 2007), and may as well reduce the risk of job burnout (Oberle et al, 2020;Rey et al, 2016). Nevertheless, negative affect drops this relationship, which could lead to more vulnerability for negative health outcomes in teachers who are working in a stressful environment, dealing with interpersonal conflict in the classroom on a daily basis (Federici & Skaalvik, 2012;Pryce & Frederickson, 2013;Valente & Lourenço, 2020).…”
Section: Article In Pressmentioning
confidence: 80%
See 1 more Smart Citation
“…Our results showed that negative affect has an important impact on teachers' health, by restraining the benefits of EI on burnout symptoms. These findings provide additional evidence that increasing emotional abilities are directly linked with lower levels of work-related stress (Extremera et al, 2007), and may as well reduce the risk of job burnout (Oberle et al, 2020;Rey et al, 2016). Nevertheless, negative affect drops this relationship, which could lead to more vulnerability for negative health outcomes in teachers who are working in a stressful environment, dealing with interpersonal conflict in the classroom on a daily basis (Federici & Skaalvik, 2012;Pryce & Frederickson, 2013;Valente & Lourenço, 2020).…”
Section: Article In Pressmentioning
confidence: 80%
“…Research consistently shows that teachers who possess the ability to accurately perceive, understand, express, and regulate emotions are considered be more effective in achieving academic goals, maintaining social relationships, and generating a favorable classroom environment and discipline practices (Augusto-Landa et al, 2011;Castillo-Gualda et al, 2017;Di Fabio & Kenny, 2016;García-Arroyo & Segovia, 2018;Pryce & Frederickson, 2013;Valente & Lourenço, 2020). In addition, most teachers have experienced the repercussions of poor emotional abilities; for instance, teacherstudent relationship may be affected by an inappropriate display of disrespect for student's feelings (Buri et al, 2019;Mérida-López & Extremera, 2017;Oberle et al, 2020).…”
Section: Article In Pressmentioning
confidence: 99%
“…En cambio, los profesores y profesoras que sienten estrés o agobio por sus responsabilidades como educadores tienen dificultades para manejar su clase, lo que afecta a su bienestar y al rendimiento académico del alumnado (Atmaca et al, 2020;Lavy y Eshet, 2018). Así mismo, los alumnos detectan estos síntomas de estrés crónico en el profesorado, informando sobre una interacción entre profesor-alumno menos positiva y con falta de apoyo (Oberle et al, 2020).…”
Section: Palabras Claveunclassified
“…Así, las personas participantes señalan que las dinámicas del programa les permitieron desarrollar relaciones de cooperación basadas en el compañerismo, la igualdad, el respeto y la aceptación positiva, en un espacio de confianza y diálogo que facilitó conocerse mejor descubriendo la diversidad de opiniones y experiencias. En la actualidad, las escuelas se han convertido, en algunas ocasiones, en un lugar de trabajo inseguro y complicado para los docentes que sufren altos niveles de estrés y agotamiento emocional (Atmaca et al, 2020;Oberle et al, 2020). Por ello, la comunidad educativa está cada vez más necesitada y solicita con urgencia programas que se basen en la cooperación y fomenten el apoyo social (Ju et al, 2015).…”
Section: Conclusionesunclassified
“…Despite the growing interest in understanding student-teacher relationships, much of the extant empirical research examining the impact of teacher SECs on student-teacher relationships has focused on teachers of younger students in elementary schools (Yoon, 2002;Mashburn et al, 2006). Nonetheless, there is now an emerging corpus of research investigating associations between teacher characteristics and student-teacher relationships in early adolescence (Longobardi et al, 2016;Oberle et al, 2020). For example, Braun et al (2019) found that middle school teachers' self-reports of mindfulness were significantly and positively related to observer ratings of the quality of emotional support in teachers' interactions with their students.…”
Section: Introductionmentioning
confidence: 99%